Mining Customer Experiences of Hybrid Customized Cultural Fashion: The Case of High-End Qipaos for Weddings - Zhongjie Wang; Chuanlan Liu; Zhixiu Li (Journal of Theoretical and Applied Electronic Commerce Research)
Consumer experiences with cultural fashion for special events often involve heightened expectations, with satisfied customers typically demonstrating increased brand engagement and loyalty. Traditional cultural attire, such as the Chinese Qipao, is widely recognized as quintessential for expressing cultural identity and fashion sensibility, particularly for weddings and other significant life events. Understanding these consumer experiences is crucial for cultural fashion brands seeking to expand their customer base by strategically enhancing consumer satisfaction through providing innovative features. This study, which examines customer experiences with hybrid customized high-end Qipaos for weddings using the integrated customer value framework, seeks to identify value dimensions that lead to satisfied customers. LDA and thematic analyses reveal three predominant themes. Specifically, the theme of “style”, reflecting esthetic values, emerged as the most influential factor and drives customer satisfaction, favorable word of mouth, and referrals. The theme of “fit”, representing performance values, was identified as a basic product feature and functions as a dissatisfier that customers take for granted when customizing high-end traditional cultural attire. This study used a dictionary-based analysis to examine consumers’ price, service, and traditional element preferences. This study proposes a five-dimensional value framework for assessing the high-end expressive fashion customization processes and experiences from a customer value perspective. The findings theoretically expand consumer value theory within customized consumption and offer practical recommendations for e-commerce brands and customization enterprises, aiming to enhance customer satisfaction.